Analyser les pôles du sens de l’activité pour accompagner les nouvelles prescriptions du travail - Aurélie Landry; Sandrine Caroly (Activités)
Over recent years, numerous changes in the workplace have transformed the organizational framework of activity. The evolution of prescription modifies activity and creates conflicts or inconsistencies. The 3 poles of the meaning of activity are put in tension by these evolutions. In this article, we define the 3 poles of meaning in activity, drawing on recent work on the meaning of work, and knowledge of the characteristics of the task that promote or hinder meaning. A meaningful activity is one in which the operator's sensibility, the meaning of his activity and his environment, and the direction he wishes to give to his activity are coherent and can be expressed. We will illustrate the value of this approach using an example of intervention that aims to support a robotics design project. In conclusion, an analysis of the activity’s meaning within an intervention highlights the essence of the activity, one that is shared by everyone in the work group, and which needs to be preserved or developed as the prescription evolves.